Sonochemical synthesis and characterization of uniform lanthanide orthophosphate (LnPO4, Ln = La and Ce) nanorods - Phuruangrat A. (2014)
Uniform lanthanide orthophosphate (LnPO4, Ln = La and Ce) nanorods were successfully synthesized by a simple ultrasonic irradiation method using lanthanide nitrate salt (Ln(NO3)3·6H2O, Ln = La and Ce) and sodium phosphate (Na3PO4) in aqueous solutions with the pH of 1-3. The products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectrometer (FT-IR), and UV-visible (UV-Vis) spectroscopy. In this research, the products are nanorods of monoclinic LaPO4 and hexagonal CePO4 structures and the vibration modes of PO4 3-, including the strong peaks at 227 nm for LaPO4, and at 225 and 278 nm for CePO4. © 2014 The Nonferrous Metals Society of China and Springer-Verlag Berlin Heidelberg.